Foreign languages teaching on cross-cultural basis: applied aspect (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article deals with the issue of foreign languages teaching (Ukrainian, English, German, Hebrew) on а cross-cultural basis. It substantiates the validity of using a cross-cultural component as a significant factor in foreign language mastering inasmuch as diversity of cultures in the world is an important step to intellectual ethnic enrichment, which can lead to misunderstanding among the representatives of one or other cultures.The paper analyses the works of the scientists, who highlight the dependence of successful communication and interaction between communicants on the level of culture concepts knowledge, rules of moving from sphere of concepts to lexical and semantic system with account of understanding of culture implementation norms.The authors developed method guidelines, tasks, exercises, which would conduce formation of the skills of effective use of communicative means during foreign information perception, comprehension and reproduction, achievement of mutual understanding in foreign culture medium, communication within linguistic behaviour tactics, which comply with native speakers’ language and culture traditions.To form person’s cross-cultural competence, a basic unit of foreign material is represented by texts, system of dialogues, polylogues, which includes providing information on certain aspects of different cultures (values, traditions, customs, holidays, verbal / non-verbal behaviour patterns), on shaping of abilities and skills of culture-specific items identification with their further use in accordance with the context; of overcoming verbal and non-verbal communication barriers (knowledge about gestures, mimics, poses, sight, handshake).
Keywords: cross-cultural component; foreign languages teaching; English; German; Ukrainian as a foreign language; Hebrew; system of tasks and exercises